2017
DOI: 10.1016/j.gaitpost.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal and plantar pressure patterns of 1000 healthy individuals aged 3–101 years

Abstract: This study has established whole of life normative reference values of widely used spatiotemporal and plantar pressure parameters, and revealed changes to be expected across the lifespan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
84
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 54 publications
5
84
1
7
Order By: Relevance
“…Peak plantar pressure refers to the maximum pressure value recorded in a predetermined region of the foot during the gait cycle (Melai et al, 2011). For the YFA the highest peak pressure under the plantar foot has been found at BT area which was in line with to previous the previous study (Kernozek & Lamott, 1995;McKay et al, 2017) that the maximum pressures and maximum pressure changes occurred in the forefoot (Soames, 1985). But the result of this study also found some difference with the previous study.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Peak plantar pressure refers to the maximum pressure value recorded in a predetermined region of the foot during the gait cycle (Melai et al, 2011). For the YFA the highest peak pressure under the plantar foot has been found at BT area which was in line with to previous the previous study (Kernozek & Lamott, 1995;McKay et al, 2017) that the maximum pressures and maximum pressure changes occurred in the forefoot (Soames, 1985). But the result of this study also found some difference with the previous study.…”
Section: Discussionsupporting
confidence: 82%
“…The main finding of this study was that the TG shown greatest peak pressure and pressure time integral in the FM while the YFA shown biggest peak pressure and pressure time integral in the BT. When comparing the two groups, the walking speed was found to be similar in both TG and YFA which was consistent with the result that the gait velocity was stable from adolescence through to adulthood and there was no difference in the self-selected gait velocity of children and older adults (McKay et al, 2017). Peak plantar pressure refers to the maximum pressure value recorded in a predetermined region of the foot during the gait cycle (Melai et al, 2011).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations